Graft survival of fourth‐time renal transplant recipients is similar to third‐time recipients: A SRTR database analysis. Issue 7 (10th May 2020) - Petrun, Branden M.; Christie, Robert; Nygaard, Rachel M.; Israni, Ajay; Hill, Mark J.; Richardson, Chad J.; Stahler, Paul A.
Abstract: Background: Candidates for repeat kidney transplant (KT) have increased. While graft and patient survival are inferior to primary KT, second and third KTs improve patient survival over dialysis. Little is known about the outcomes after fourth KTs. Methods: We retrospectively compared characteristics of third and fourth KTs in the SRTR. Factors associated with graft survival in third vs fourth KT and patient survival of fourth KT vs patients waitlisted for a 4th KT were assessed by Cox regression and multivariable linear regression analysis. Results: There were 3055 third‐ and fourth‐time KTs performed in the United States. Fourth‐time graft survival was not significantly different from third‐time transplants (HR 1.06, P  = .653). Patients who received a fourth KT have a significant survival advantage compared with patients who remained on the waitlist for a fourth KT (HR = 0.53, P  = .006). Conclusions: Graft and patient survival of fourth KTs are comparable to third KTs, but inferior to first and second KTs in terms of graft and patient survival. Recipients of fourth KT have had an increased life expectancy compared with patients waitlisted for a fourth KT.